IMPROVEMENTS IN THE TRANSMISSION OF VOLTAGE EVAPORATION PULSES IN THE ATOM-PROBE - Sijbrandij, S; Cerezo, A; Smith, G (1995)
A new arrangement for the transmission of voltage evaporation pulses in time-of-night atom probe instruments has been designed and implemented. A key feature in the design is the use of a flexible 50 Omega coaxial pulse line, continued within the vacuum system, to avoid reflections and losses in transmission. This allows the pulse to reach the specimen stage almost free from distortions or increase in risetime. A counter-electrode is used in this design, to which negative pulses are applied to produce field evaporation of the specimen. Mass resolutions achieved are approximately m/Delta m = 300 full width at half maximum.